Time analysis of policies in the banking sector - a field study - aamer alaraaji; asem alaraaji (Iraqi Journal for Administrative Sciences, 2024)
Chaos and corruption are usually condemned in almost every where and in every time. For the purpose of dealing scientifically with each of these negative phenomena number of research projects were carried out. The on-going transition towards what is called NOW. has precipitated an increasing trend towards non-linear dynamism in different World affairs and, by its turn , precipitated certain observable parallel between corruption and chaos where each of theme aims at weakening institutionalism in organizations. As a result, organizations are caught in a vicious cycle. Corruptive activities facilitate chaotic interventions and vice versa. The objective of this research project is to look for possibilities of salvation of institutionalism form the vicious cycle as needed.